If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y = yz + 10 Reorder the terms: Y = 10 + yz Solving Y = 10 + yz Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Simplifying Y = 10 + yz
| -8(-8x-6)=-6x-222 | | s+7(4)=16 | | 193=3+10p | | -3(-3+y)+3y=4 | | -5m=-85 | | -7(x+4)=0 | | 6n-2(3-n)=-13 | | 44+2c=7c-6 | | x/13=-7 | | 3x+3/3= | | 6(2m-1)-1(11m+6)=7 | | 7x-11=17-7x | | 60-2m=8m | | 7+14=16 | | 6x-7+3x=10+9x-7 | | 13=3x-6 | | 3-10+1-5= | | y=z+x-8/w | | 14=p/2 | | 4z=2.5+2.7 | | 27=0.5x(2+7) | | 9-1/2b=5+8/2b | | xx=42 | | 4k^2-13k+3=0 | | 8-(4y-9)=5-5y | | -3x+22/2= | | (x-1/2)=(2-x/3) | | 5.4/-4.5y | | -10?4(3p?10)=18 | | -3x+9+3x=4 | | .2(5+2x)=4(.3x+.9) | | 4c=4 |